STRATEGI KONSERVASI HABITAT UNTUK MEMPERTAHANKAN KEANEKARAGAMAN IKAN DI RAWA LEBAK SUNGAIRUNGAN, PALANGKARAYA, KALIMANTAN TENGAH [Habitat conservation strategy to maintain fish diversity in the Rungan River Floodplain, Palangkaraya, Central Kalimantan] - Bambang Sulistiyarto; Dedi Soedharma; M. F. Rahardjo; Sumardjo Sumardjo (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2007)
The largest fraction of freshwater fish diversity is presented in floodplain ecosystem. Moreover, floodplain fisheries in Kalimantan have an important contribution to local community livelihoods. Floodplain ecosystems are faster to be damage and loss than other ecosystems. Consequently, conservation of fish habitat is urgently needed to maintain fish diversity. The objectives of this study were to give strategies of fish habitat conservation for maintaining fish diversity, based on biophysical and social analysis. Studies were carried out in Petuk Ketimpun District of Palangkaraya Municipality. Biophysical variables were studied by monthly samples taken from May 2005 to April 2006. These were carried out at three stations with different habitat type, includes forested swamp, opened swamp, and river. Social and cultural information collected by interviewing with fishers and local government agencies. A total of 4278 fishes were collected consisting of 50 species and 19 families. Forest swamps and river are habitat priorities to be conserved. The conservation of forest swamps is directed to maintain of the habitat structure, while the conservation of river is directed to maintain water quality and to maintain river as fish refuge site at low water season. Fishery regulation is priority used for maintaining fish diversity in opened swamps.